Distribution function of plasma particles in axial magnetic and radial electric fieldsfor the transverse injection of neutral gas - Chibisov, D.V. (Вопросы атомной науки и техники, 2016)
The distribution function of particles in plasma which is created in crossed axial magnetic and radial electric
fields by ionization of gas is obtained. It is assumed that the neutral gas before its ionization rotates with a constant
angular velocity and the gas particle velocity distribution function in rotating frame is Maxwellian. Produced plasma
particles move in crossed fields without collisions. The obtained distribution function is written in the coordinates of
the guiding center. The expressions for the distribution function in the various special cases are also obtained. Получена функция распределения частиц в плазме, которая создаётся в скрещённых осевом магнитном и
радиальном электрическом полях. Предполагается, что нейтральный газ перед ионизацией вращается с по-
стоянной угловой скоростью, а функция распределения частиц газа по скоростям во вращающейся системе
отсчёта является максвелловской. Образовавшиеся частицы плазмы движутся в скрещённых полях без
столкновений. Полученная функция распределения записана в координатах ведущего центра. Получены
также выражения для функции распределения в различных частных случаях. Отримано функцію розподілу частинок у плазмі, яка утворюється в схрещених осьовому магнітному і
радіальному електричному полях. Передбачається, що нейтральний газ перед іонізацією обертається зі ста-
лою кутовою швидкістю, а функція розподілу частинок газу за швидкостями в обертовій системі відліку є
максвеллівською. Утворині частинки плазми рухаються в схрещених полях без зіткнень. Отримана функція
розподілу записана в координатах ведучого центру. Отримано також вирази для функції розподілу в різних
окремих випадках.